Negative impact of imflammation and insulin resistance on the biogenesis of HDL-c in Indonesian men with metabolic syndrome (Faculty of Medicine Universitas Indonesia, 2010)
Aim To find out the relationship between inflammation and insulin resistance with impaired HDL biogenesis that cause low HDL-c concentrationMethods Using a cross-sectional design, this study involved 163 adult men, aged 25-60 years old with metabolic syndrome (IDF criteria, 2005), without liver and kidney dysfunction. This study was undertaken in Jakarta in the year 2007-2009. Measured indicators were serum apolipoprotein A-1 (apoA-1), prebeta-1 HDL, cholesteryl ester transfer protein (CETP), HDL cholesterol (HDL-c), body weight, height, waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood glucose (FBG), and triglyceride. The apoA-1/HDL-c ratios were taken as indicator of HDL maturation, whereas CETP/HDL-c and CETP/TG ratios were indicated HDL catabolism. high-sensitivity CRP (hsCRP) and HOMA-IR were taken as indicator of inflammation and insulin resistance, respectively. Data were analyzed by using univariate, bivariate, and multivariate analysis.Results Positive correlations were found between hsCRP and CETP (rs= 0.200, p= 0.042), and CETP/HDL-c ratios (rs= 0.188, p= 0.013). HOMA-IR positively correlated with apoA-1/HDL-c ratios (rs= 0.190, p= 0.016) and negatively correlated with the CETP/TG ratios (rs= -0.162, p= 0.04). Results of general linear model analysis showed that serum hsCRP concentration had the highest contribution to CETP/HDL-c ratios, apoA-1, dan CETP (p= 0.009; 0.016; 0.054, respectively).Conclusions Inflammation and insulin resistance related to dysfunction of HDL biogenesis in men with metabolic syndrome. The inflammation correlated with increased HDL catabolism, whereas the insulin resistance correlated with decreased HDL maturation and increased HDL catabolism. These may lead to low HDL-c concentration. Inflammation had higher contribution to HDL biogenesis factors than insulin resistance. (Med J Indones 2010; 19:36-45)Keywords: hsCRP, HOMA-IR, apoA-1, prebeta-1 HDL, CETP, HDL-c and metabolic syndrome